Freedom of Expression in the Era of Democracy: Records of Human Rights Enforcement - Della Luysky Selian; Cairin Melina (Universitas Negeri Semarang, 2018)
Since the rollout of reform in 1998, discourse and democratic movements have occurred massively and widely in Indonesia. UNESCO research results state that perhaps for the first time in history, democracy is stated as the best and proper name for all systems of political and social organization championed by its influential supporters. This paper tries to see how the fulfillment and protection of freedom of expression in Indonesia and its relation to Human Rights.